PENERAPAN SHALAT DHUHA DALAM PENINGKATAN MORAL SISWA DI SEKOLAH - Kandiri Kandiri; Mahmudi Mahmudi (Edupedia : Jurnal Studi Pendidikan dan Pedagogi Islam, 2018)
The moral decline of students is felt by many side, both school and community. The existence of engage in gang fight among them,their oppressionto teachers, drugs, etc. Those are moral phenomenon of students need to be changed. Many efforts can be done by school to overcome that moral phenomenon. One of them is performing dhuha in a congregation in school. This kind of salatwhich held in the morning is expected to withstand the bad students’behavior afterwards. The incantations contained in dhuhaif contemplated can lead the students to submit and obey to the teachings of Islam.This wisdom is actually contained in the implementation of salat in general, of coursein the implementation of dhuha.